“The real modernity that is here”: understanding the role of digital visualisations in the production of a new urban imaginary at Msheireb Downtown, Doha - Melhuish, C; Degen, M; Rose, G (Wiley, 2016)
This paper explores how Computer Generated Images (CGIs) have enabled the visualisation and negotiation of a new urban imaginary in the production of a large‐scale urban development project in Doha, Qatar. CGIs were central not only to the marketing but also the design of Msheireb Downtown. Our study of their production and circulation across a transnational architectural and construction team reveals how their digital characteristics allowed for the development of a negotiated, hybridised urban imaginary, within the context of a re‐imaging and re‐positioning of cities in a shifting global order. We suggest that CGIs enabled the co‐production of a postcolonial urban aesthetic, disrupting the historical Orientalist gaze on the Gulf region, in three ways. Firstly, they circulate through a global network of actors negotiating diverse forms of knowledge from different contexts; secondly, they are composed from a mix of inter‐referenced cultural sources and indicators visualising hybrid identities; and thirdly, they evoke a particular urban atmosphere which is both place‐ and culture‐specific, and cosmopolitan. The study emphasises the importance of research into the technical and aesthetic production processes which generate new urban spaces in the context of global market‐led growth; and, by considering the circulation of CGIs between sites, contributes to the development of “a more properly postcolonial studies” (Robinson 2011, 17). [Urban Development; Digital Visualisation; Doha, Postcolonial Studies]